Chemico-physical features of soot emitted from a dual-fuel ethanol–diesel system. (15th June 2015) - Gargiulo, V.; Alfè, M.; Di Blasio, G.; Beatrice, C.
Highlights: Significant concentration decrease of the emitted particles. No significant increment of oxygen amount in soot by changing the ethanol loading. Soot features slightly vary with the increasing amount of injected ethanol. Abstract: The paper describes an experimental study aimed to characterize the impact of the dual-fuel ethanol–diesel combustion system on size, number and chemical characteristics of the emitted carbonaceous particles. The tests were conducted on a single cylinder research engine provided with a modern architecture and properly modified in a dual-fuel (DF) configuration. In particular, the experimental campaign was aimed to evaluate in detail the effect of the use of the ethanol as port injected fuel in diesel engine on the size distribution function, morphology, reactivity and chemical features of the exhaust emitted soot particles. The engine tests were chosen properly in order to represent actual working conditions of an automotive light-duty diesel engine. The morphological and chemical features of soot particles were studied in dependence of the ethanol–diesel substitution rate by analyzing the soot collected at the engine exhaust. Results indicated a significant effect of ethanol fumigation on the concentration of the emitted particles but not on the average size, as well as, a negligible impact of ethanol premixed charge on the soot nanostructural features.